Fraud Triangle Sebagai Pendeteksi Kecurangan Laporan Keuangan - Wahyuni Wahyuni; Gideon Setyo Budiwitjaksono (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2017)
The financial statements arestructured representation of the financialposition shows the financialperformance of an entity. On the other hand, the FinancialServices Authority in Indonesia gave the sanction to capital market players for cheatingFinancial Statements.This shows that the financial statement fraud cases occurring inIndonesia are part of the failure of an audit conducted by the Public Accounting Firm(KAP).This study aims to examine the influence of fraud triangle in detectingfraudulent financial statements. The object of this study using the financial statementsof companies listed on the Indonesia Stock Exchange in the 2012-2014 time period.This study uses 123 data samples are taken using purposive criteria. The data wereanalyzed using multiple linear regressionanalysis.The results showed thatrazionalization significant effect on the financial statements fraud. Meanwhile, thefinancial stability, external pressure, financial targets, the nature of the industry,ineffective monitoring did not significantly affect the financial statements fraud. Thisstudy contributes to the regulators to adopt measures to improve the quality of audits,especially in detecting fraud.